Koncepcja controllingu w stacji socjalnej - Dyczkowski, Tomasz (The Concept of Controlling in a Social Station., 2006)
The paper presents the example of the controlling system as being implemented by a German charity. The first part briefly characterizes a social station and gives an overview of its operation. The next section describes major reasons for developing a controlling system in the organization in question and lists its objectives. The system of management reports and key ratios is outlined subsequently. Eventually, the further challenges and necessary adjustments of the organization work are put forward.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 89-96